INTEGRATING PSYCHOLOGICAL INTERVENTIONS IN THE DIAGNOSIS AND TREATMENT OF RECURRENT CERVICAL CANCER: A MULTIDISCIPLINARY APPROACH (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Recurrent cervical cancer remains a formidable global health challenge, with a 5-year survival rate of less than 20% for advanced stages, imposing profound physical, emotional, and social burdens on patients. The psychological impact of recurrence is particularly severe, as patients grapple with heightened anxiety, depression, fear of mortality, and existential distress, which significantly impair treatment adherence, quality of life, and overall prognosis